PEMURIDAN PEMBERDAYAAN BAGI JEMAAT DISABILITAS DALAM PELAYANAN MIMBAR DI GEREJA INKLUSIF - Innawati Innawati (STT Amanat Agung, 2021)
Abstract: The Church belongs to the Lord and is the extension of the Lord's hand in the world. The Church is open to all people, but in church’s services, there are still discriminations, especially against members with disabilities. This research conducted in the Jemaat Kristen Indonesia (JKI) Bukit Sion Mangliawan is a follow-up study of the previous research, namely “The Discipleship for Congregations with Disabilities in Church M Malang”. The method used is experimental research that observes and analyzes changes resulting from X treatment on Y in controlled situations. The conclusions of the experimental research in the JKI Bukit Sion Mangliawan proved the hypothesis that member with disability was able to serve well like non-disabled ones in the service of the Word at local church. This proved that empowerment of discipleship in an inclusive church was a solution to the problem of marginalization of the empowerment of congregations with disabilities in the service of the Word at local church. Empowering discipleship in an inclusive church was most appropriate for anyone, whether the members of congregations with disabilities or not. Keywords: service of the Word, discipleship, empowerment, congregation with disability, inclusive church. Abstrak: Gereja adalah milik Tuhan dan perpanjangan tangan Tuhan di dunia. Gereja terbuka untuk semua manusia, tetapi di dalam pelayanan gereja masih terjadi diskriminasi, khususnya terhadap jemaat penyandang disabilitas. Penelitian ini yang dilaksanakan di gereja Jemaat Kristen Indonesia (JKI) Bukit Sion Mangliawan, merupakan penelitian lanjutan dari penelitian sebelumnya yaitu “Pemuridan bagi jemaat penyandang disabilitas di Gereja M Malang”. Metode yang digunakan adalah penelitian eksperimen; mengamati dan menganalisa perubahan akibat perlakuan X terhadap Y dalam situasi yang terkendalikan. Simpulan dari hasil penelitian eksperimen di gereja JKI Bukit Sion Mangliawan membuktikan hipotesa bahwa jemaat penyandang disabilitas mampu melayani dengan baik seperti orang non-disabilitas dalam pelayanan mimbar di dalam gereja lokal. Hal ini membuktikan bahwa pemuridan pemberdayaan di gereja inklusif sebagai solusi bagi masalah marjinalisasi pemberdayaan jemaat penyandang disabilitas dalam pelayanan mimbar di gereja lokal. Pemuridan pemberdayaan di gereja inklusif adalah yang paling tepat bagi siapa saja, baik jemaat penyandang disabilitas maupun bukan. Kata-kata kunci: pelayanan mimbar, pemuridan, pemberdayaan, jemaat penyandang disabilitas, gereja inklusif.